Pengaruh Store Atmosphere dan Kualitas Pelayanan terhadap Kepuasan Konsumen ER Cofffe Pekanbaru - Putri, Yulita Nabilla; Sutrisna, Endang (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2023)
The study was conducted at Er Coffee. The purpose of this study is to determine the influence of the store atmosphere and service quality on customer satisfaction at Er Coffee Pekanbaru. Store atmosphere as an independent variable (X1) and service quality as an independent variable (X2) and customer satisfaction as a dependent variable (Y). The problem in this study is that there is fluctuation in the realization of the number of consumers, this is accompanied by the café business increasing every year as can be seen from the data of café competitors. The sample of this study was taken as many as 97 respondents calculated using the Slovin formula. The data obtained from the questionnaire results using the Accidental Sampling technique and then processed to be tested with statistics through the SPSS 23 program. The results of this study show that the results of testing the store atmosphere t test hypothesis on consumer satisfaction, namely t count (8,568) > t table (1,661) means that store atmophere affects consumer satisfaction. Second, the quality of service to customer satisfaction obtained a calculated value (8,279) > t table (1,661) meaning that the quality of service affects customer satisfaction. F store atmosphere test results and service quality have a significant effect on customer satisfaction, namely F count (58,131) > Ftabel (3.09). This means that simultaneously the store atmosphere and service quality have a significant effect on customer satisfaction at Er Coffee Pekanbaru Keywords : store atmosphere, service quality and customer satisfaction.